Design, Simulation and Fabrication of Band Pass Filter 308 MHz Narrow Bandwidth Using Technology Surface Mount Technology (SMT) on FMCW Radar Frequency Generators - I Dewa Putu Hermida; Deni Permana Kurniadi; Iqbal Syamsu (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Has been research a band pass filter with a steep slope the working frequency 308MHz with 4 MHz bandwidth used in navigation radar system. To overcome this, the design is done by using two filters are combined. Merger This filter consists of a single filter consisting of a low pass filter with a cutoff frequency that works at a frequency of 310 MHz, and a high pass filter with a cutoff frequency that works at a frequency of 306 MHz Type filter is used to generate the elliptic filter steepness better by ignoring the ripple in the pass band for narrow bandwidth. For a low pass filter, stop band width (Fs) approximately 20% of the cutoff frequency occurs at a frequency of 372 MHz, with stop band depth (As) of about -55 dB As for the high pass filter, stop band width (Fs) approximately 20% of the cutoff frequency that occurred at a frequency of 244.8 MHz, with stop band depth (As) of about -55 dB. The output filter is used as a clock on direct insert digital synthesizer (DDS). Using the components of surface mount technology (SMT), then the resulting circuit with its small dimensions, compact and has a high Q. Elsie used in the simulation stage software version 2.72, the manufacturing process using protel 99SE, and the stage of measurement using a vector network analyzer (VNA) Advantest R3770 type.